Salmonella in a Brazilian pork production chain: occurrence, diversity, virulence genotypes and antibiotic resistance profile - Viana, Cibeli (2020)
Salmonella spp. is considered one of the main foodborne pathogens associated to food poisoning outbreaks worldwide. Salmonella strains have been detected in several countries. The aim of this study was to track Salmonella spp. contamination in pork production chain during slauthering and processing. Also, the aim was to provide a deep characterization of the isolates by molecular analysis. The collections were carried out in ten different farms, which were selected based on the existence of an intensive breeding system with a similar number of pigs in all the farms (average 1000), and the same company provided the piglets and feed. All selected pig farms sent stock to the same slaughterhouse. At pig farms, the following samples were collected: feed from the top of feeder pigs (n=10), water from the bite drinkers (n = 10), barn floor (n = 100). After transport, pigs were sampled at the slaughterhouse including the lairage floor (n=10, as sampled in barn floors), swine carcasses (10 carcasses per lot, n = 100), blood samples (n = 100), processing environment (n = 120), and pork cuts (n = 40). Also, portions of diaphragm (n = 100), palatine tonsils (n = 100) and mesenteric lymph nodes (n=100) were sampled from each pig carcass after evisceration. Blood and meat juice were subjected to ELISA to detect antibodies against Salmonella, and other samples were subjected to Salmonella detection by ISO 6579. After confirmation the isolates were subjected to serogrouping, macro- restriction digests and pulsed-field gel electrophoresis (PFGE), detection of virulence-related genes and antimicrobial-resistance phenotyping. Also, 41 isolates were selected to whole- genome sequencing. Salmonella was recovered from barn floors from 3 pig farms (3/10), lairage floors (7/10), carcasses after bleeding (2/100) and final washing (1/100), palatine tonsils (45/100), mesenteric lymph nodes, (43/100), utensils (3/120) and cuts (4/40). The most prevalent serogroup was O: 4 (82%) followed by O:3 (7.7%); O:9 (5.1%); O:8 (2.6%) and O:7 (2.6%). Based on ELISA, Salmonella positive samples were: 86 and 46 blood serum (20% and 40% cut-offs) and 68 and 46 meat juice (20% and 40% cutoffs). Optical density readings from blood serum and meat juice presented a high and significant correlation (r = 0.93, p < 0.001). Recovered strains (n = 109) were classified into 24 different pulsotypes (XbaI restriction digest), which were arranged into five different clusters. Fourteen different virulence genotypes were observed based on 15 loci, and all isolates were positive for invA, sitC, pagC and tolC. Whole-genome sequencing and in silico serotyping demonstrated that the S. enterica serovar Typhimurium was the most common serotype (n = 17), but eight additional servoars were identified. Eight multilocus sequence types were identified with ST19 being most common (n = 21). Several plasmids replicons were detected, with Col (RNAI) the most abundant (n = 30), followed by IncR (n = 22), IncI1 (n = 10) and IncA/C2 (n = 10). High rates os resistance were observed, mainly to streptomycin, tetracycline, ampicillin, chloramphenicol and ciprofloxacin. Only two isolates were resistant to third-generation cephalosporins and no isolates were resistant to two tested carbapenems. Twenty-six unique antimicrobial-resistance genes were identified with bla TEM-1A and bla TEM-1B likely responsible for most beta-lactam resistance and floR responsible for most chloramphenicol resistance. At the time of collection, the sampled farms were adding ciprofloxacin to feed, and this may have contributed to the high prevalence of resistance to this antibiotic. A majority of isolates were considered multidrug resistant (resistant to 3 or more antibiotic classes). This study provides valuable insight about the epidemiology of Salmonella in swine production. Despite the low presence of this pathogen in carcasses and meat cuts, the presence of the pathogen in lymph nodes and tonsils emphasizes the importance of slaughterhouse hygiene measures. Considering the antimicrobial resistance global scenario, the high occurrence of multidrug resistant isolates from pork production is a serious data. The antibiotic use must be controlled, and it is recommended that antibiotics considered to be of critical importance to human health should be avoided in animal use. Keywords: Ciprofloxacin. ELISA. MLST. Swine. WGS.